Joint Beamforming Optimization for Simultaneously Transmitting And Reflecting (STAR) RIS Aided Communications : (Invited Paper) - Mu, Xidong; Liu, Yuanwei; Xu, Jiaqi; Guo, Li; Lin, Jiaru (Conference record - Asilomar Conference on Signals, Systems, & Computers, 2021)
A novel concept of simultaneously transmitting and reflecting (STAR) reconfigurable intelligent surfaces (RISs) is investigated, where the incident wireless signal is divided into transmitted and reflected signals passing into both sides of the space surrounding the surface, thus facilitating a full-space manipulation of signal propagation. Motivated by this unique feature, a STAR-RIS aided downlink communication system is considered, where a multi-antenna base station (BS) sends information to two users, i.e., one on each side of the STAR-RIS. A power consumption minimization problem for the joint optimization of the active beamforming at the BS and the passive transmission and reflection beamforming at the STAR-RIS is formulated, subject to communication rate constraints of the users. The resulting highly-coupled non-convex optimization problem is solved by an iterative algorithm, which exploits the penalty method and successive convex approximation. Finally, our numerical results reveal that the required power consumption is significantly reduced by employing the proposed STAR-RIS instead of conventional reflecting/transmiting-only RISs.